Child-Friendly Green Transportation Week at Sekolah Alam Lampung: Early Education on Sustainable Mobility - Shahnaz Nabila Fuady; Goldie Melinda Wijayanti; Verlina Agustine; Fachri Muhammad Rasyid; Chania Rahmah (Unram Journal of Community Service, 2026)
Sustainable and child-friendly transportation is a critical issue in environmentally conscious and inclusive urban development; however, its understanding remains largely limited to adult populations. This community-based research aims to enhance early awareness of sustainable mobility through the implementation of the Green Child-Friendly Transportation Week at Sekolah Alam Lampung. The program was designed using an Education for Sustainable Development (ESD) framework, employing participatory, visual, and experiential learning approaches. The activities included interactive educational sessions, the use of innovative learning media, student mini-projects, and the active involvement of teachers as learning facilitators. Evaluation methods comprised pre-test and post-test assessments, observations, and teacher reflections. The results indicate a notable improvement in students’ understanding of green transportation concepts, the relationship between transportation modes and emissions, and the health risks associated with mobility. Student-generated mini-projects, such as educational posters, simple prototypes, and sketches of child-friendly transportation routes were found to enhance critical thinking skills, creativity, and context-based problem-solving abilities. Beyond student outcomes, the program also strengthened teachers’ capacity to integrate sustainable mobility themes into thematic school learning. Furthermore, dissemination through social media, video documentation, and online mass media expanded the program’s impact beyond the school community to the wider public. Overall, the findings demonstrate that experiential and visual-based educational approaches are effective in fostering sustainable mobility values and environmental awareness among school-aged children.